The Impact of CSR-Harmonious on Financial Performance: Moderating Role of Green Entrepreneurial Intellectual Capital - Iswari, Hanif Rani; Wardhana, Ery Tri Djatmika Rudijanto Wahju; Handayati, Puji; Restuningdiah, Nurika; Soetjipto, Budi Eko; Wardoyo, Cipto; Pratikto, Heri (GOVERNORS, 2023)
The purpose of this research is to investigate the role of green entrepreneurial intellectual capital as a moderator of the influence of Corporate Social Responsibility Harmonious (CSR-H) on the financial performance of SMEs in the creative industry game developer sub-sector in Malang City. SMEs in the game developer sub-sector are included in businesses that utilize the results of creativity supported by technology so that it is one of the business fields that is closely related to intellectual capital. Related to awareness of green entrepreneurship, the echo developer sub-sector is appropriate if it integrates it into green entrepreneurial intellectual capital. Thus, green entrepreneurial intellectual capital in this case is the focus of attention for research as a moderation between Corporate Social Responsibility Harmonious (CSR-H) and Financial Performance. This research is a quantitative approach with a survey method on SMEs in the game developer sub-sector. The sample population taken was 20 respondents. Questionnaires are distributed using a likert scale. Data analysis uses SmartPLS version 3. The findings of this study obtained Corporate Social Responsibility Harmonious (CSR-H) is not significant to financial performance, Green entrepreneurial Intellectual Capital is positively significant to financial performance and Green entrepreneurial intellectual capital does not moderate the effect of Corporate Social Responsibility Harmonious (CSR-H) on financial performance. Keywords: Corporate Social Responsibility, CSR Harmonious, Green entrepreneurial, Green intellectual capital, Financial Performances